EMPIRICAL AND POSITIVISTIC SOCIOANALYSES AND THE AMAZON - Barbosa, Cloves; Wilson Tafner Junior, Armando (Journal of Interdisciplinary Debates, 2025)
The behaviourist science began with Francis Bacon and It yours developments until to Comte’ positivism. It jointed most person of the modern science. This philosophy is influence over modern into the thought about science. it has the focus about actual social order’ conservation.